Extremity War Injuries IX. Issue 8 (August 2015) - Andersen, COL Romney C.; Schmidt, Andrew H.; Fitzgerald, CAPT Brian T.; Tintle, LCDR Scott M.; Helgeson, MAJ Melvin D.; Lehman, LTC Ronald A.; Davila, COL Jeffrey N.; Potter, Benjamin K.; Burns, MAJ Travis C.; Swiontkowski, Marc F; Ficke, COL James R.
<x xml:space="preserve">Abstract</x> Extremity War Injury Symposium IX focused on reducing disability within the military, centering on cartilage defects, amputations, and spinal cord injury. Many areas of upper and lower extremity trauma and disability were discussed, including segmental nerve injuries, upper extremity allotransplantation, and the importance of patient-reported functional outcomes compared with the traditionally reported measures. Strategic planning addressed progression toward clinical solutions by setting clear objectives and goals and outlining pathways to address the "translation gap" that often prevents bridging of basic science to clinical application.